Needs Analysis for Developing Interactive Science Learning Media Based on the Local Wisdom of Traditional Foods in Nganjuk Regency for Elementary School Students - Putri Ningtyas, Dinni; Suprapto, Nadi; Suryanti; Julianto (Didaktika Tauhidi: Jurnal Pendidikan Guru Sekolah Dasar, 2025)
The needs analysis is an initial activity aimed at achieving learning objectives, including in science education. This needs analysis provides information as a reference for the development of learning media. The objective of this study is to analyze the need for the development of interactive learning media based on local wisdom of The Great Regency for fifth-grade students of SDN 1 Tirtobinangun. The research used a descriptive analysis method, interviews, and questionnaires as data collection instruments. Based on the results of this study, it can be concluded that the needs analysis for the development of interactive learning media based on local wisdom of The Great Regency received positive feedback. This study can be further developed in the creation of interactive learning media based on local wisdom of The Great Regency on the human digestive system material for fifth-grade students of SDN 1 Tirtobinangun.